Time‐resolved electroabsorption measurement of carrier velocity in inverted polarity In1‐xGax N/GaN heterostructures due to internal electric fields. Issue 3 (27th February 2014) - Connelly, Blair C.; Gallinat, Chad S.; Woodward, Nathaniel T.; Enck, Ryan W.; Metcalfe, Grace D.; Tompkins, Randy; Jones, Kenneth A.; Shen, Hongen; Wraback, Michael
Abstract: Carrier transport measurements were made in a c ‐plane inverted‐polarity n ‐GaN/ i ‐In1– x Ga x N/ p ‐GaN heterostructure with a 200 nm thick In1– x Ga x N layer using ultrafast spectroscopy techniques. Time‐domain THz measurements indicate that the direction of electron transport is dominated by drift towards the n ‐GaN layer. Time‐resolved electroabsorption measurements were used to determine carrier velocities by monitoring the change in transmission of a probe beam tuned to the In1‐ x Ga x N absorption edge due to the transport of photogenerated carriers under the built‐in internal electric field. Carrier transit times associated with screening of the electroabsorption are resolved at the lowest injection level. The signal rise time shows two distinct time scales, which correspond to an electron velocity of 3.3 ± 0.5 x 10 7 cm/s and a hole velocity of 6.7 ± 0.3 x 10 6 cm/s in an internal electric field of ∼150 kV/cm. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)